Evaluation of bacterial pathogens in neonatal sepsis and their susceptibility pattern: A Hospital Based Study (Community Based Medical Journal, 2014)
Neonatal sepsis is one of the major causes of neonatal morbidity and mortality, particularly in developing countries. Epidemiology and surveillance of neonatal sepsis helps in implementation of rational empirical antibiotic strategy. A cross-sectional prospective study was conducted in the special care baby unit under department of Paediatrics and Neonatology, BIRDEM General Hospital during the period of November 2008 to September 2009 to determine the pattern of bacterial agents causing neonatal sepsis and their susceptibility pattern to various antimicrobial agents. Blood cultures were performed on admitted newborn babies (0-28 days) to rule out sepsis. Antimicrobial susceptibility testing was done for all blood culture isolates according to the criteria of the National Committee for Clinical Laboratory Standards by disk diffusion method. Out of 720 screened blood cultures, 64 (8.9%) reported as positive and the gram positive and gram negative bacteria accounted for 6 (9.4%) and 58 (90.6%) respectively. The most common gram positive organisms were Staphylococcus aureus (6.3%) and Enterococci (3.1%) & gram negative organisms were Klebsiella pneumoniae (37.5%), Serratia (25%), Pseudomonas aeruginosa (10.9%), Citrobacter (10.9%) and Acinetobacter (6.3%). The susceptibilities were remarkably low to Ampicillin (3.12 %) & Cefotaxim (10.9%) for both gram positive & gram negative isolates. Gram positive group had susceptibilities of 66.7% to Ciprofloxacin and Imipenem, 83.3% to Gentamicin, & 100% to Amikacin & Vancomycin. Gram negative isolates showed higher sensitivities to Imipenem (94.8%), Ciprofloxacin (89.7%), Amikacin (72.4%) respectively. Gram-negative bacteria showed high level of resistance to commonly used antibiotics (Ampicillin, Ceftazidim and Cefotaxim). Gentamicin, Amikacin, Imipenem and Ciprofloxacin were the most effective drugs compared to others. Routine bacterial surveillance and their sensitivity patterns must be an essential component of neonatal care.CBMJ 2014 January: Vol. 03 No. 01 P: 35-40